2001
DOI: 10.4049/jimmunol.167.10.5887
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Stimulates the MyD88-Independent Pathway and Results in Activation of IFN-Regulatory Factor 3 and the Expression of a Subset of Lipopolysaccharide-Inducible Genes

Abstract: Bacterial lipopolysaccharide (LPS) triggers innate immune responses through Toll-like receptor (TLR) 4, a member of the TLR family that participates in pathogen recognition. TLRs recruit a cytoplasmic protein, MyD88, upon pathogen recognition, mediating its function for immune responses. Two major pathways for LPS have been suggested in recent studies, which are referred to as MyD88-dependent and -independent pathways. We report in this study the characterization of the MyD88-independent pathway via TLR4. MyD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
713
5
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 978 publications
(762 citation statements)
references
References 52 publications
39
713
5
5
Order By: Relevance
“…Two such molecules, MyD88 and Mal/TIRAP, have already been reported to play a role in TLR-4-induced TNF␣ and IL-6, but not IP-10, production (63,64). It has been suggested that IP-10 production requires the activation of interferon-regulatory factor 3 (65), and this may depend on the adapter molecule TRIF/TICAM-1, another recently identified MyD88 homolog (66,67). Thus, distinct adapter molecules of TLR-4 are likely to engage alternative signaling pathways and alternative kinases involved in I B␣ phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Two such molecules, MyD88 and Mal/TIRAP, have already been reported to play a role in TLR-4-induced TNF␣ and IL-6, but not IP-10, production (63,64). It has been suggested that IP-10 production requires the activation of interferon-regulatory factor 3 (65), and this may depend on the adapter molecule TRIF/TICAM-1, another recently identified MyD88 homolog (66,67). Thus, distinct adapter molecules of TLR-4 are likely to engage alternative signaling pathways and alternative kinases involved in I B␣ phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the TLR4 ligand lipopolysaccharide (LPS) can still trigger activation of NF-kB in Myd88-deficient mice, albeit with delayed kinetics compared with wild-type cells, whereas most other TLRs are completely ineffective at activating NF-kB in these mice [13]. Although Myd88-deficient mice lose their ability to produce proinflammatory cytokines, such as TNF, IL-1, IL-6 and IL-12 p40, in response to LPS, they retain their capacity to produce IFN-inducible genes and co-stimulatory molecules and their dendritic cells (DCs) mature in response to LPS [14,15]. These studies define two arms of the LPS signalling pathway: a Myd88-dependent component that promotes fast activation of NF-kB and induction of proinflammatory molecules and a Myd88-independent pathway (also used by TLR3) that mediates slow activation of NF-kB and induction of IFN-inducible genes and costimulatory molecules (Figure 1).…”
Section: Myd88-dependent Signalling and Activation Of Nf-kbmentioning
confidence: 99%
“…The engagement of TLR3 and TLR4 by poly(I:C) and LPS, respectively, promotes phosphorylation of IRF3 and the induction of type I IFN genes [14,32,33]. An intense research effort culminated in key reports identifying two kinases responsible for this phosphorylation [34,35].…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 99%
“…In addition to this common pathway, TLR4 utilizes a MyD88-independent signaling pathway that results in the activation of interferon regulatory factor 3 (IRF-3), the induction of type I interferons, and the maturation of dendritic cells [9][10][11][12]. The adaptor protein TIR-domaincontaining adaptor inducing IFN-g ([TRIF]; also called TICAM-1) was recently demonstrated to activate IFN-g expression via IRF-3 and to associate with both TLR3 and IRF-3 [13,14].…”
Section: Introductionmentioning
confidence: 99%